2021
DOI: 10.1159/000518997
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Mapping of Proton Therapy, Heavy Ion Therapy, and Helical Tomotherapy for Gastric Cancer

Abstract: <b><i>Purpose:</i></b> This study aimed to systematically present application situation and therapeutic effect of proton therapy (PT), heavy ion therapy, and helical tomotherapy (TOMO) for gastric cancer (GC), and to find gaps of existing studies. <b><i>Methods:</i></b> PubMed, EMBASE, the Cochrane Library, Web of Science, and Chinese Biological Medical Database were searched. Tables, bubble plot, and heat map were conducted to display results. <b><i>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Evidence mapping in oncology has also seen an expansion beyond cancer treatments [39][40][41][42][43][44][45][46][47][48] to include molecular pathogenesis, 49 risk factors, 50,51 complications 52 and nutritional intervention. 53 Nicholson et al 54 proposed the usage of citation index and tools that incorporate artificial intelligence in helping researchers to find relevant scientific literature, as searching for the most highly cited papers in an area of interest is one of the possible approaches for sifting and dealing with massive numbers of publications.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence mapping in oncology has also seen an expansion beyond cancer treatments [39][40][41][42][43][44][45][46][47][48] to include molecular pathogenesis, 49 risk factors, 50,51 complications 52 and nutritional intervention. 53 Nicholson et al 54 proposed the usage of citation index and tools that incorporate artificial intelligence in helping researchers to find relevant scientific literature, as searching for the most highly cited papers in an area of interest is one of the possible approaches for sifting and dealing with massive numbers of publications.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to include evidence mapping for cancer have so far covered therapeutic interventions, clinical management, alternative treatments, and adjunctive testing. [55][56][57][58][59][60][61][62][63] A limitation of this report is the possibility of unintended citation selection bias. As the chapter authors were invited to contribute to the Blue Book based on their publication record, there might understandably be an inclination to include publications that they had participated in, reflecting their subject expertise and publication content familiarity.…”
Section: Discussionmentioning
confidence: 99%
“…of studies which applied this method showed 39 publications from 2003 to 2015, but none surfaced for pathology. Efforts to include evidence mapping for cancer have so far covered therapeutic interventions, clinical management, alternative treatments, and adjunctive testing 55–63 …”
Section: Discussionmentioning
confidence: 99%